The phenomenon of labor migration as a determining factor of global problems - Hetmanseva, Nina; Кіріяк; Kiriiak, Оксана; Oksana; Козуб, Ирина (My University, 2021)
Based on a theoretical analysis, the most urgent problems of labor migration as a legal phenomenon that is global in nature and carries both positive and negative features that depend on the subjective and objective factors of the region of each country are characterized. The relationship of labor migration to the potential for economic development of the country is shown. The focus is on the need for the legislative attention of the national legislator to the mechanisms of legal protection of labor rights of migrants.
Keywords: labor migration; migration policy; migration processes; economic strategy; labor resources